Chemical shift transfer: an effective strategy for protein NMR assignment with ARTINA - Wetton, Henry; Klukowski, Piotr; Riek, Roland; Güntert, Peter (Frontiers in Molecular Biosciences, 2023)
Chemical shift transfer (CST) is a well-established technique in NMR spectroscopy that utilizes the chemical shift assignment of one protein (source) to identify chemical shifts of another (target). Given similarity between source and target systems (e.g., using homologs), CST allows the chemical shifts of the target system to be assigned using a limited amount of experimental data. In this study, we propose a deep-learning based workflow, ARTINA-CST, that automates this procedure, allowing CST to be carried out within minutes or hours of computational time and strictly without any human supervision. We characterize the efficacy of our method using three distinct synthetic and experimental datasets, demonstrating its effectiveness and robustness even when substantial differences exist between the source and target proteins. With its potential applications spanning a wide range of NMR projects, including drug discovery and protein interaction studies, ARTINA-CST is anticipated to be a valuable method that facilitates research in the field.This is a provisional file, not the final typeset articleThe exact amount of experimental data required for de novo chemical shift assignment with ARTINA depends on the signals' resolution and signal-to-noise ratio. Typically, the requirement for the measurement time on expensive NMR spectrometers scales to approximately one or two weeks.